Differences In Students' Motivation by Socio-Economic Status Of Parents And Their Implications In Guidance And Counseling - Yulita Wardhani; Asmidir Ilyas (Jurnal Neo Konseling, 2019)
Motivation to learn is a strong impulse in students that raises activities for learning, guarantees the continuity of learning activities, one of the factors that influence students 'learning motivation is parents' socio-economic status. this research aims to : (1) learning motivation of students in schools with the condition of the upper and middle class socioeconomic status, (2) learning motivation of students in schools whose parents' social status is up and down, (3) learning motivation of students in schools with a condition of middle-class parents with lower social status, (4) identify differences in student learning motivation based on parental socio-economic status and its implications in guidance and counseling.This type of research is quantitative research with descriptive comparative method. The population of this study was as many as 800 students of Banuhampu Middle School 01 District. Agam and a sample of 187 students were selected by proportional random sampling technique. The instrument used was a questionnaire form of Likert scale. Data were analyzed by using descriptive statistics and test different techniques (analysis of variance) with SPSS for Windows version 20.00.The findings showed that: (1) The students' motivation social status on the high category, (2) The students 'motivation medium social status in the high category, (3) the social status of students' motivation under the category of being, and (4) there is a significant difference between students' motivation social status upper, middle and lower.